Best Management Practices in the Everglades Agricultural Area: Fertilizer Application Control - Timothy A. Lang; Samira H. Daroub; Orlando A. Diaz; Ming Chen (EDIS)
This EDIS document is one in a series of publications that provide current implementation guidelines for commonly employed BMPs that target the reduction of P loads leaving EAA farms via drainage water. This document is SL-232, a fact sheet of the Soil and Water Science Department, UF/IFAS Extension. Original publication date January 2006.